Photovoltaic thermal (PVT) air collector with monofacial and bifacial solar cells: a review - Fudholi, Ahmad; Mustapha, Muslizainun; Taslim, Ivan; Aliyah, Fitrotun; Gani Koto, Arthur; Sopian, Kamaruzzaman (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
Photovoltaic thermal (PVT) collectors directly convert solar radiation into electrical and thermal energy. A PVT collector combines the functions of a PV panel and a flat plate solar collector. The development of PVT air collectors is a very promising research area. At present, PVT air collectors are used in solar drying and solar air heaters. On the basis of existing literature, most PVT air collectors were built by using monofacial PV modules. The bifacial PV modules had two active surfaces that could capture solar radiation with its front and rear surfaces. Additional sunlight absorption through both surfaces resulted in an enhanced electrical power generation compared with the conventional monofacial PV. Therefore, bifacial PVT was considered to be useful and attractive due to its potential of enhancing overall system performances, including energy and exergy efficiencies. Findings of this review indicated that PVT air collector with bifacial solar cell produced a larger amount of electrical energy, which was approximately 40% higher than a monofacial PVT. The energy and exergy efficiencies of PVT air collector with monofacial solar cells range from 27% to 94% and from 4% to 18%, respectively. For bifacial PVT, the energy and exergy efficiencies of PVT air collector range from 28% to 67% and from 8.2% to 8.4%, respectively.